Urokinase-Type Plasminogen Activator Inhibits Efferocytosis of Neutrophils - Yang, Yanping (American Thoracic Society, 2010)
Rationale: Phagocytosis of apoptotic cells, also called efferocytosis, plays an essential role in the resolution of inflammation. Urokinase-type plasminogen activator (uPA) is a multifunctional protein that has been implicated in inflammatory conditions, including pneumonia and severe infection, which are often accompanied by the development of acute lung injury. However, the role of uPA in modulating efferocytosis of apoptotic neutrophils has not been defined. Objectives: To characterize the role of uPA in regulation of efferocytosis and to delineate the underlying mechanisms involved in this process. Methods: In vitro and in vivo phagocytosis, immunoprecipitation, and Western blotting assays. Measurements and Main Results: The phagocytosis of apoptotic neutrophils by macrophages was significantly inhibited by uPA. Mutant uPA lacking the growth factor domain and catalytically inactive uPA had similar inhibitory effects on efferocytosis, as did wild-type uPA. In contrast, absence of the kringle domain abrogated the ability of uPA to diminish efferocytosis. Both the α(V)β(3) integrin and vitronectin seemed to be involved in the inhibition of efferocytosis by uPA. Incubation of macrophages with uPA also diminished activation of the small GTPase Rac-1, which normally occurs during ingestion of apoptotic neutrophils. Under in vivo conditions in the lungs, uPA decreased the uptake of apoptotic neutrophils by alveolar macrophages. Conclusions: Our data demonstrate a novel role for uPA in which it is able to diminish the uptake of apoptotic neutrophils by macrophages under both in vitro and in vivo conditions.